Upaya meningkatkan hasil belajar IPS tentang Sejarah Kemerdekaan Indonesia dengan media gambar melalui model Bertukar Pasangan untuk siswa kelas V pada SDN Binturu kabupaten Tabalong - Ristinawati Ristinawati (Program Studi PGSD STKIP PGRI Banjarmasin, 2019)
This study aims to improve student learning outcomes in the history of Indonesian independence through models of exchanging pairs using picture media, increasing the activity of students and teachers in the learning process in class V of SDN Binturu, Kelua District, Tabalong Regency. This research is a Classroom Action Research which is designed as many as 2 cycles with each cycle of 2 meetings. Each cycle consists of the stages of Planning, Acting, Observing, and Reflecting. At the end of each cycle a reflection or evaluation is carried out to determine the developments that occur and to determine the next strategy in learning by using media images and videos through a model of exchanging partners. The research subjects were fifth grade students of Binturu Elementary School. The method of collecting learning outcomes is taken through tests at the end of each meeting and at the end of each cycle, while the activities of teachers and students are taken through observation during the teaching and learning process. Data analysis techniques are used with frequency distribution techniques, percentages, and interpretations. The results of this study indicate that strengthening character education in elementary school The results of this study indicate that the average student learning outcomes are 69.50 in the first cycle of meetings 1, 73.67 in the first cycle of meeting 2, 64.42 in the second cycle of meetings 1 and 82 , 08 in the second cycle of meeting 2. The evaluation of the cycle test also experienced an increase of 77.50 in the cycle I and 87.50 in the cycle II test. In line with these learning outcomes, the level of classical completeness also increased, namely 66.67% in the first cycle of meeting 1, 70.83% in the first cycle of meeting 2, 70.83% in the first cycle test, 79.17% in the second cycle of the meeting 1, 83.33% in the second cycle of meeting 2 and 87.50% in the cycle II test. Student activity also increased, namely 59.38% in the first cycle of meeting 1, 62.50% in the first cycle of meeting 2, 75% in the second cycle of meeting 1 and 81.25% in the second cycle of meeting 2. Besides that, the activity of the teacher also experienced the increase in the implementation presentation was 53.57% in the first cycle of meeting 1, 60.71% in the first cycle of meeting 2, 77.22% in the second cycle of meeting 1 and 98.75% in the second cycle of meeting 2.